Exploring the Anti-Inflammatory Potential of Choerospondias axillaris Through Molecular Docking based in silico Pharmacological Investigation - Shrestha, Sabin; Shrestha, Ayusha; Raut, Bechan; Thapa, Rahi Bikram; Adhikari, Pharsuram; Khanal, Dharma Prasad; Ghimire, Abisa; Raut, Sabita; Paudel, Roshan; Shrestha, Prawol Narayan (Journal of Manmohan Memorial Institute of Health Sciences, 2026)
Introduction: Inflammation is an adaptive response that occurs due to harmful stimuli. Short-term inflammation is a vital protective response, but prolonged inflammation leads to various illnesses, and conventional anti-inflammatory drugs often cause adverse effects. Choerospondias axillaris, a medicinal plant traditionally used has demonstrated potential anti-inflammatory activity. This study aimed to evaluate the anti-inflammatory potential of different active chemical constituents through in silico investigation.Method: In-silico method was utilized to identify potential active chemical constituents of Choerospondias axillaris as anti-inflammatory agents. PyRx integrated version of AutoDock, open babble, vina wizard and Biovia discovery studio were utilized to predict the scoring functions with specific protein Cyclooxygenase - II (PDB-ID: 6COX). Discovery studio visualizer and marvin sketch was used to create 2D and 3D structure, interaction, and various web server was utilized to predict and collect the data.Result: Twenty-one active chemical constituents of Choerospondias axillaris were designed and docked with protein Cyclooxygenase - II (PDB-ID: 6COX. Binding affinity of the standard drug diclofenac shows -7.4 kcal/mol, two hydrogen bonds, Asn A:375 and His A: 226 with Protein [6COX], whereas AS-11 shows highest binding affinity -10.5 kcal/mol, four hydrogen bonds, Glu B: 465, Asp B: 125, Ala B:151, Tyr B:130, AS-20 shows binding affinity -10.3 kcal/mol, nine hydrogen bonds, Pro A:154, Gln A:461, Asn A:39, Glu A:465, Ala A:151, Gly A:45, Cys A:41, Tyr A:130, Leu A:152 and AS-13 shows binding affinity -10.1 kcal/mol, four hydrogen bonds, Cys B :36, Tyr B: 130, Arg B: 44, Glu B :465 with protein [6COX]. All active chemical constituents have good Physiochemical, Pharmacokinetic parameters, Lipinski’s Rule (except AS-19) but almost all ligands show Nephrotoxicity and respiratory toxicity further lead optimization is needed.Conclusion: Our in-silico investigation reveals that different types of active chemical constituents present in Choerospondias axillaris have different level interaction with Cyclooxygenase – II (PDB-ID: 6COX) on the basis of scoring function. Out of twenty-one ligands (AS-11) Quercetin-3-Arabinoside, (AS-13) Quercetin-3-Rhamnoside, and (AS)-20 Epicatechin Gallate might shows excellent anti-inflammatory activity on the basis of Insilco data.